A Generalized Homogeneously Weighted Moving Average Monitoring Scheme for Monitoring the Process Mean - Maonatlala Thanwane; Malela-Majika, Jean-Claude; Frans Kanfer; Kashinath Chatterjee (Contemporary Mathematics, 2025)